EFFECTS OF TEMPERATURE VARIATIONS AND PRE-SOWING TREATMENTS ON THE GERMINATION OF Milicia excelsa: A CASE STUDY OF SEEDS COLLECTED FROM BENCHI-MAJI ZONE, SOUTH-WESTERN ETHIOPIA - Mohammed Adefa Seid; Yigardu Mulatu Mengesha (APTKLHI, 2023)
Seeds always exhibit some degree of dormancy, resulting in a delay and irregularity of germination, and the seeds of Milicia excelsa often have seed germination difficulty. The main objective of this study was to demonstrate the seed germination variations of M. excelsa at room temperature (20-25°C) and incubator (25.6o C). In this study, 400 seeds of M. excelsa were tested using three pre-sowing treatments and control. Each treatment was defined as four replications in which 25 seeds per replication were initially sown in a 90 mm diameter petri dish with disc paper in a completely randomized design. The result showed that the mean germination percentage of the control treatment scored about 23.8%, followed by seeded rubbed by hand with a score of 15%. It is observed that room temperature has a significant effect (29%) on the germination of the control treatment compared to the incubator (18.7%) at p=0.05. However, no significant mean germination difference is observed between the effects of room temperature and the incubator in the remaining pre-sowing treatments: Washed with tap water (T1), 2) Washed and soaked in hot water for 15 minutes (T2) and 3) rubbing by hand (T3). However, it can be inferred that room temperature is an ideal temperature that meets plants' physiological seed germination requirement. To understand the importance of temperature and light on the germination of angiosperm, further experiments involving variable ranges of temperature and light intensity can be conducted.